Gambaran Personal Hygiene Perawat dalam Upaya Pencegahan Infeksi Luka Operasi di Rumah Sakit Umum Daerah Haji Makassar (Indo-MathEdu Intellectuals Journal, 2026)
Surgical site infections (SSI) are one of the most common types of nosocomial infections occurring in hospitals. Nurses' personal hygiene, including hand hygiene practices and the use of personal protective equipment (PPE), plays a crucial role in preventing SSI. The aim of this study was to describe the personal hygiene of nurses in the prevention of surgical site infections at Haji Hospital Makassar. This study employed a descriptive quantitative design with a cross-sectional approach. A total of 153 nurses were selected using a total sampling technique. The research instrument was a questionnaire that had been tested for validity and reliability. The results showed that most nurses had good personal hygiene, particularly in the aspects of hand hygiene and PPE use. However, some nurses were still inconsistent in implementing self-cleanliness according to standards. In general, nurses’ personal hygiene at Haji Hospital Makassar was categorized as good in preventing surgical site infections, although improvements in compliance and consistency are still required. The hospital is expected to strengthen supervision, provide supporting facilities, and conduct regular training on personal hygiene and infection prevention for all nurses